(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
An important problem of modern higher education pedagogy is the formation of highly qualified specialists in any field of human activity. Physical training is an important component of the system of training cadets of higher education institutions in the security and defense sector. For future border guards, physical training is the basis of their professional activity, and it is given primary attention during training. The analysis of ways and possibilities of further development of the personality can take place within the framework of new approaches in the field of education, on the research of which scientists from different countries are directing their efforts. In addition to traditional educational concepts that have already gained recognition, new approaches and concepts are being sought. This creates a need for scientific research into new approaches, effective tools and methods that can help improve approaches to the physical training of cadets. Recently, a new scientific approach has been actively developing - acmeology, which considers development as constant improvement, and its result - the achievement of the individual and society. Acmeology comes from the Greek "acme" - the top, the highest point of something. This is a relatively new scientific field, which includes a complex of scientific disciplines that study a person in the process of his self-development, self-improvement and self-determination in various spheres of life and self-realization. This new aspect of scientific research requires a revision of traditional ideas about human development, emphasizing the role and importance of a mature personality in modern conditions. In this regard, it is advisable to consider the possibilities of this approach to improving the physical training of cadets.